Analisis Kelayakan Investasi Kandang Tertutup pada Peternak Ayam Broiler Plasma PT Gema Usaha Ternak, Yogyakarta - Purnomo, Sutrisno Hadi; Santosa, Krishna Agung (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2007)
This research is aiming at finding the feasibility of close house investment of broiler farmers of Plasma PT Gema Usaha Ternak from the financial point of view. The research was conducted by collecting primary and secondary data. The primary data, consisting of house size, number of birds, investment cost, operational and raising costs and farmer’s revenue, were obtained from the broiler farmers of plasma PT Gema Usaha Ternak. The secondary data, consisting of standard house investment cost, operational and raising costs, the current prices, and farmers’ revenue, were gained from PT Gema Usaha Ternak. Both primary and secondary data were then analyzed, observing the net present value, profitability index, discounted payback period and internal rate of return. The result of financial analysis was sensitively tested with changing some cost structures. The proving of the first hypothesis revealed that close house investment were financially feasible. The result of sensitivity analysis with some changes in cost structure showed that the more the farmers used  their own capital the more feasible it would be. The result of analysis on aspects of techniques and technology, marketing, operational management, and social-environment showed that close coop investment was feasible. Key words : broiler farmers, feasibility analysis, sensitivity analysis